2014
DOI: 10.1208/s12248-014-9707-3
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Amphiphile Micelles Self-Adjuvant Group A Streptococcal Vaccination

Abstract: Abstract. Delivery system design and adjuvant development are crucially important areas of research for improving vaccines. Peptide amphiphile micelles are a class of biomaterials that have the unique potential to function as both vaccine delivery vehicles and self-adjuvants. In this study, peptide amphiphiles comprised of a group A streptococcus B cell antigen (J8) and a dialkyl hydrophobic moiety (diC 16 ) were synthesized and organized into self-assembled micelles, driven by hydrophobic interactions among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 61 publications
(106 reference statements)
1
83
0
Order By: Relevance
“…19,20 In our previous studies, micelles were used as a vaccine delivery vehicle that induced a peptide-specific antibody response. 21 Interestingly, PAMs stimulated a stronger antibody response than peptide alone without the use of an adjuvant making it a self-adjuvanting device. Furthermore, while the hydrophobic tails enhance cell uptake by anchoring into cell membranes, 22 they do not act as pathogen recognition receptor (PRR) agonists and therefore do not function as molecular adjuvants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 In our previous studies, micelles were used as a vaccine delivery vehicle that induced a peptide-specific antibody response. 21 Interestingly, PAMs stimulated a stronger antibody response than peptide alone without the use of an adjuvant making it a self-adjuvanting device. Furthermore, while the hydrophobic tails enhance cell uptake by anchoring into cell membranes, 22 they do not act as pathogen recognition receptor (PRR) agonists and therefore do not function as molecular adjuvants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while the hydrophobic tails enhance cell uptake by anchoring into cell membranes, 22 they do not act as pathogen recognition receptor (PRR) agonists and therefore do not function as molecular adjuvants. 21 Rather, it is thought to be the self-assembled, particular-based physical nature of PAMs that affords them immunogenicity. Self-assembly of PAs has the added benefit of being able to facilitate the fabrication of multifunctional heterogeneous micelles through simple mixing of different PAs or other amphiphilic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…They annealed the micelles at 70 • C to form stable long fibrils while preserving the alpha helical secondary structure. These micelles induced high IgG1 antibody titres without the assistance of TLR-2 receptors in BALB/c mice and HEK-293 cells expressing the TLR-2 receptor [190]. This study demonstrated that micellization of the peptide amphiphiles enhanced the delivery of antigens in their correct conformation.…”
Section: Vaccine Design Using Lipidated Peptide Amphiphilesmentioning
confidence: 68%
“…This theme issue also includes several original research articles. Tirrell and colleagues report on recent progress in the development of peptide amphiphile micelles that selfadjuvant group A streptococcal vaccinations [9]. In their report, a streptococcus B lymphocyte antigen and a dialkyl hydrophobic moiety were covalently linked and underwent self-assembly into micelles when added to water, due to the hydrophobic interactions among the alkyl tails.…”
mentioning
confidence: 99%
“…These include peptide amphiphile micelles [9], pH responsive polymer-based nanoparticles [10], cationic liposomes [11], polysaccharide-based nanoparticles [12], and nanoparticles formed from biodegradable polymers such as p o l y l a c t i c -c o -g l y c o l i d e ( P L G A ) [ 1 3 -1 5 ] and polyanhydrides [16]. This theme issue includes a comprehensive review by Jewell and colleagues on the topic of harnessing biomaterials to engineer the lymph node microenvironment for immunity or tolerance [17].…”
mentioning
confidence: 99%